Análisis de la calidad molinera en 14 genotipos de arroz (Oryza sativa L. ssp. indica) cultivadas en el área del proyecto CEDEGE, cantón Babahoyo, provincia de Los Ríos. - Vélez Chávez, Jean Paúl (2018)
SUMMARY The present research on “Analysis of milling quality in 14 genotypes of rice (Oryza sativa L. ssp. indica) cultivated in the area of the CEDEGE project, Babahoyo canton, province of Los Ríos”. Was conducted in the FERGONZA company, canton Lomas de Sargentillo, province of Guayas, located at km 47 via Manabí, Ecuador. The objectives of this research were: To measure the milling properties of 14 Indica-type rice genotypes, and to identify milling properties and the differences among them. the Completely Random Design (DCA) was used for the statistical analysis of milling quality variables, using an ANAVA. The Tukey test was also applied at 5% significance. Principal component analysis, cluster analysis and relative variability, also were applied. Fourteen varieties of rice with four replicates were used. The varieties evaluated were: BA-100-UTB, BR-101-UTB, CA-102-UTB, FE-103-UTB, FI-104-UTB, FI-105- UTB, FI-106-UTB, FI-107-UTB, SH-108-UTB, FL109-UTB, FL-110-UTB, G-111-UTB, G-112-UTB and G-113-UTB. In the procedure, a mini milling equipment was used, model THP-3, 0.35 HP at 1720 RPM, CHEN SAN FUMG brand, which served to shelling, polish, get the dust and the broken grains. The moisture content of the samples was 11%. The variables that were evaluated were: percentage (%) of impurity, percentage (%) of humidity, density of the grain (g / L), length of the grain with husk (mm), weight (g) of husk, weight (g) of brown rice, weight (g) of white mass, weight (g) of polished powder, weight (g) of broken grains, weight of rice flower and length of polished grain (mm). Related to the results, the weight of husk and the weight of white mass were not statistically significant, the remaining variables were highly significant (5%). In this study it was determined that there are cultivars with good miller characteristics similar to the commercial varieties that currently exist in Ecuador. The varieties that showed the best yields of flower rice were G-112-UTB, FE-103-UTB and FI-107-UTB and the varieties BA-100-UTB, FI-105-UTB and FL-110-UTB reached the higher density (g / L). It is recommended to conduct studies on rice crop management using the available technologies to determine its effect on milling quality, to measure mainly the density parameter (g / L), which reflects whether a crop has been well managed or not and finally, it is recommended to plant rice varieties in different rice sectors to determine their effect on mill quality versus sensory quality. Keywords: Rice, Cultivars, Milling Quality, Flower Rice, Grain Density.